Simulated STAT Laboratory in a University Based Medical Laboratory Science Program. - OJA, JANET; THOMAS, JANICE; NICHOLAOU, MATTHEW (Clinical Laboratory Science)
A crucial component of Medical Laboratory Science (MLS) student training is clinical experience. This can be delivered through clinical rotations or by clinical laboratory simulation. Weber State University (WSU) in Ogden, Utah utilizes a combination of both to provide clinical experience to MLS students. In response to feedback from bi-yearly meetings with an advisory board, a campus simulated laboratory course was re-designed to enhance student customer service, communication skills, workflow and time management, instrument maintenance and troubleshooting, data entry, and result reporting. The course was modeled after a hospital STAT, or small core, laboratory consisting of blood bank, coagulation studies, chemistry, hematology, urinalysis, microbiology, and specimen processing. The course was taught over two semesters and evaluated by a pre/post survey related to the main educational outcomes, a mock certification exam, and a comprehensive practical exam. The survey results showed that the students' perceived competence increased in all the areas of training, with the greatest increases seen in specimen processing and management and communication. The lowest average score was demonstrated in perceived competence with instrument maintenance. All students achieved a department-required minimum 80 percent competence on the comprehensive practical exam and there was a significant increase (p<0.001) in mock certification exam scores.